2017
DOI: 10.1007/s00464-017-5979-x
|View full text |Cite
|
Sign up to set email alerts
|

Early laparoscopic adhesiolysis for small bowel obstruction: retrospective study of main advantages

Abstract: Early laparoscopic surgery can be proposed as an effective alternative treatment for ASBO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…From a pathophysiological standpoint, it is well accepted that adhesions occur within seven days following the peritoneal injury, becoming progressively organized with brotic tissues. On average, patients must be readmitted twice over the subsequent 10 years due to such adhesions [2,6]. Acute PID primarily cause paralytic ileus, while recurrent chronic pelvic viscera adhesion mainly result in mechanical ileus [4,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a pathophysiological standpoint, it is well accepted that adhesions occur within seven days following the peritoneal injury, becoming progressively organized with brotic tissues. On average, patients must be readmitted twice over the subsequent 10 years due to such adhesions [2,6]. Acute PID primarily cause paralytic ileus, while recurrent chronic pelvic viscera adhesion mainly result in mechanical ileus [4,7].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the most common causes of SBO are intestinal adhesions, tumors, hernias, and in ammatory bowel disease, 10% of which may be further due to infection or in ammation (e.g. appendicitis, diverticulitis, endometriosis, pelvic in ammatory disease (PID), intestinal disease, abdominal tuberculosis), or chemical peritonitis and irritation caused by foreign bodies [2,3]. Thirty-three percent of SBO occur in the rst year following the triggering factor [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Placing anti-AA barriers is costly and needs extra operative time, therefore barriers positioning should be preferentially targeted in selected high-risk cases 35 . Patients with AA and chronic abdominal pain have been approached with laparoscopic adhesiolysis but the procedure is still controversial, often causing other AA in a vicious circle and it is not clear if adhesiolysis leads to a substantial pain relief, preservation of female fertility or improvement in quality of life 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Experienced laparoscopic surgeons extended their applications and performed laparoscopy for SBO surgeries. 2 Multiple studies and reports comparing laparoscopy and open surgery have revealed safety and feasibility of laparoscopic surgery and also postoperative short-term advantages of laparoscopic treatment for SBO including less postoperative pain, and faster recovery. 3 Furthermore, single port laparoscopic surgery also is being used for the maximal benefits of minimally invasive surgery.…”
Section: Editorialmentioning
confidence: 99%